PEMINDAHAN HAK ATAS KEKAYAAN YAYASAN MENURUT UNDANG-UNDANG NOMOR 16 TAHUN 2001 JO UNDANG-UNDANG NOMOR 28 TAHUN 2004 TENTANG YAYASAN - M. Rizky Faizha Putra; T. Keizerina Devi Azwar; Ramli Siregar (Universitas Sumatera Utara, 2013)
The transfer of property rights foundation in regard to the provisions set forth in Law No. 16 year 2001 yo Act No. 28 of 2004 (